2000
DOI: 10.1093/nar/28.18.3511
|View full text |Cite
|
Sign up to set email alerts
|

Parallel intramolecular DNA triple helix with G and T bases in the third strand stabilized by Zn2+ ions

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Interestingly, by using the ChIRP technique, similar GA-enriched motifs were identified among the binding sites of the chromatin-modulating RNAs roX2 and HOTAIR , indicating that GA-enriched motifs may play an important role in the targeting of lncRNAs across the genome 19 . Previously, several studies using different techniques have shown that GA-rich homopurine sequences can form triplex structures 38 39 40 . Overrepresentation of GA-rich sequences among the genomic binding sites of the lncRNAs analysed ( MEG3 , HOTAIR and roX ) raises the possibility that the lncRNAs may be recruited to their target genes via RNA–DNA triplex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, by using the ChIRP technique, similar GA-enriched motifs were identified among the binding sites of the chromatin-modulating RNAs roX2 and HOTAIR , indicating that GA-enriched motifs may play an important role in the targeting of lncRNAs across the genome 19 . Previously, several studies using different techniques have shown that GA-rich homopurine sequences can form triplex structures 38 39 40 . Overrepresentation of GA-rich sequences among the genomic binding sites of the lncRNAs analysed ( MEG3 , HOTAIR and roX ) raises the possibility that the lncRNAs may be recruited to their target genes via RNA–DNA triplex formation.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic CD spectra of DNA triplex structures differ with the sequence of the oligonucleotide ( 64 ). However, most of the intramolecular triplex DNA show a minimum around 240 nm, a maximum around 257 nm and a second minimum at ∼280 nm ( 39 , 65 ). These peaks were also observed in the CD spectra of the TM ECO oligonucleotides.…”
Section: Resultsmentioning
confidence: 99%
“…] a different triple helical structure is formed, both with Zn 2+ and Mg 2+ [3]. Besides, specific interactions with Zn 2+ ions in low water activity conditions were found to be necessary to stabilize the parallel intramolecular DNA triple helix with G and T bases in the third strand [13].…”
Section: Introductionmentioning
confidence: 98%
“…Particularly, several different effects of zinc(II) ions on the DNA structure have been presented [1,3,4,[9][10][11]13,28,33,34].…”
Section: Introductionmentioning
confidence: 99%